2010
DOI: 10.1074/jbc.m109.078782
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Heterogeneous Ribonucleoprotein F in the Regulation of Cell Proliferation via the Mammalian Target of Rapamycin/S6 Kinase 2 Pathway

Abstract: The S6 kinases (S6Ks) have been linked to a number of cellular processes, including translation, insulin metabolism, cell survival, and RNA splicing. Signaling via the phosphotidylinositol 3-kinase and mammalian target of rapamycin (mTOR) pathways is critical in regulating the activity and subcellular localization of S6Ks. To date, nuclear functions of both S6K isoforms, S6K1 and S6K2, are not well understood. To better understand S6K nuclear roles, we employed affinity purification of S6Ks from nuclear prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 56 publications
1
36
1
Order By: Relevance
“…Interestingly, recent studies have shown that S6K2 is constitutively associated with heterogeneous ribonucleoproteins in the nucleus, and the recruitment of mTORC1 to this complex induces the activation of S6K2 upon serum stimulation. 30 This finding leads us to speculate that mTORC1 might regulate the recruitment of S6K2 to the NCoR1/PPARa complex in response to nutrient levels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have shown that S6K2 is constitutively associated with heterogeneous ribonucleoproteins in the nucleus, and the recruitment of mTORC1 to this complex induces the activation of S6K2 upon serum stimulation. 30 This finding leads us to speculate that mTORC1 might regulate the recruitment of S6K2 to the NCoR1/PPARa complex in response to nutrient levels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the importance of S6K2 in cell proliferation is illustrated in study demonstrating S6K2 was responsible for the interleukin-3 (IL-3)-driven cell proliferation since S6K2 was activated in lymphocytes and primary mouse bone marrow-derived mast cells upon IL-3 induced proliferation; and cell cycle progression was accelerated by overexpression of constitutively active S6K2 in lymphocytes (Cruz et al, 2005). Furthermore, the association of heterogeneous ribonucleoprotein (hnRNP) F with mTOR and S6K2, but not S6K1, is essential for driving cell proliferation (Goh et al, 2010). Taking collectively, both S6K1 and S6K2 are involved in mTORC1-mediated cell cycle progression.…”
Section: Mammalian Target Of Rapamycin (Mtor)mentioning
confidence: 99%
“…HnRNPs are chromatin-associated nuclear proteins that bind specifically to different RNA sequences and are involved in several steps of RNA processing, including splicing, polyadenylation, mRNA stability and translational regulation [167]. Upon serum stimulation, mTOR associates with the hnRNP-S6K2 complex and activates S6K2 which promotes cell proliferation through unknown mechanisms [120]. Recently, it was also shown that S6K2, but not S6K1, can bind to the transcription factor YY1 in serum stimulated cells [116] (Figure 10).…”
Section: Figure 12mentioning
confidence: 99%
“…However, SH3-binding motifs, which can be found in S6K2, are shown to facilitate interaction of cofactors with ERα [138], allowing to speculate that S6K2 also has the potential to act as a cofactor of the receptor. Nuclear S6K2, but not S6K1 has been shown to associate with several RNA-binding proteins, including the hnRNPs [120]. HnRNPs are chromatin-associated nuclear proteins that bind specifically to different RNA sequences and are involved in several steps of RNA processing, including splicing, polyadenylation, mRNA stability and translational regulation [167].…”
Section: Figure 12mentioning
confidence: 99%